Penghapusan Sifat Melawan Hukum Materiil Dalam Tindak Pidana Korupsi - Qadhi Muttaqien Sengaji; Ria Delta; Tian Terina (VIVA THEMIS, 2018)
Corruption in Indonesia is regulated in Law Number 31 of 1999 concerning Corruption Crime as amended by Law Number 20 Year 2001 concerning Amendment to Law Number 31 of 1999. In corruption cases after the Decision of the Constitutional Court (MK) Number 003 / PUU-IV / 2006 dated July 24, 2006, the nature of violating the material law in the Explanation of Article 2 paragraph (1) of the PTPK Law has been abolished or in other words does not have binding legal force. The Constitutional Court considers that the explanation of Article 2 paragraph (1) is contrary to the 1945 Constitution, because it creates legal uncertainty. The Constitutional Court views that Article 28 D paragraph (1) recognizes and protects citizens' constitutional rights to obtain guarantees and definite legal protection. The problems that will be examined are: how are the legal consequences of abolishing the material against the law in not corruption in Indonesia and how the judges' decisions and judgments in deciding to abolish the material against the law in the corruption case in the Constitutional Court Decision Number 003 / PUU-IV / 2006.The type of research in this paper is descriptive research. The approach method used in this study is a normative juridical approach and an empirical juridical approach. The types of data used are primary data and secondary data. Procedure for collecting and processing data through library studies and field studies by means of interviews. As well as in this study the researcher used qualitative data analysis.The results of the findings in this study are that the legal consequences of abolishing the material against the law in not corruption in Indonesia are limiting the movement of prosecutors in conducting investigations into corruption and giving corruptors the freedom to commit corruption because they can only be convicted if they can be proven committing a criminal act of corruption. Decisions and judges' judgments in deciding to abolish the material unlawfulness in corruption cases in the Constitutional Court Decision Number 003 / PUU-IV / 2006 only focus on legal certainty, and override other legal objectives such as justice and benefit of the law and do not consider values values and norms of life that grow in the community.